Serum Procalcitonin (PCT) Level In Acute Kidney Injury (AKI) In Critical Patients: Acute Kidney Injury (AKI) In Critical Patients - Iwan Tona, Azwar; Syukri, Maimun (Journal of Society Medicine, 2022)
Early prediction and avoidance of aggravation of AKI will be useful in identifying patients at risk of developing a higher degree of AKI. Many studies have been conducted to prevent AKI and find biomarkers to predict AKI. Many studies have identified biomarkers of AKI, such as neutrophil-associated lipocalin (NGAL), cystatin C, interleukin-18, and tissue inhibitors of metalloproteinase-2 (TIMP-2). Yet few have investigated the role of PCT as a predictor of AKI. The pathophysiological mechanisms that explain the association between serum PCT and AKI remain unclear. Various inflammatory responses are thought to play a role in the AKI development. PCT acts as a chemoattractant in the ​​inflammation area and causes more monocytes to invade the ​​inflammation. PCT is initially produced in adherent monocytes and then contributes to an increase in circulating PCT by attracting parenchymal cells as they attach directly to activated monocytes. High PCT levels ultimately act as a direct chemoattractant to monocyte counts.